The Role of Teachers in Overcoming Multicultural Learning Challenges for Immigrant Children (Case Study at Sungai Mulia 5 Guidance Studio, Gombak, Malaysia) - Firnasari, Ayunda Dwi; Dwijayanto, Arik (Sultan Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the role of teachers in addressing the challenges of multicultural learning among Indonesian migrant children at Sanggar Bimbingan Sungai Mulia 5 (SBSM 5), Gombak, Malaysia. Employing a qualitative approach with field research methods, the study is framed within the Asset-Based Community Development (ABCD) model. Data were collected through participant observation, in-depth interviews with the teacher (Bu Masruah), interactions with students, and supporting documentation. The findings reveal that the teacher plays multiple roles: as a cultural mediator, an emotional facilitator, and a connector between migrant children, the community, and external institutions. These roles enhance students’ engagement, motivation, and sense of belonging, although structural barriers such as legal status, limited funding, and the lack of formal recognition from local authorities persist. The study concludes that strengthening teachers’ capacity, securing formal recognition of learning centres, and fostering cross-sector collaboration are crucial for the sustainability of multicultural education for migrant children. Future research should explore cross-national collaborative strategies to strengthen inclusive alternative education models.